Empathy of Healthcare Professionals During Covid-19 Crisis - Ayesha Qaisar, Jibran Umar Ayub Khan, Iftikhar Ali Kakar, Umar Ayub Khan, Faheem Naeem Awalzai, Azlan Shah, Assad Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Empathy is one of the most vital parts of medical ethics that is a prerequisite for good clinical practice, yet the level of empathy of the doctors has not been up to the mark. Objective: To measure empathy of healthcare professionals during COVID-19 crisis Materials and Methods: This was a cross Sectional Study done in almost all public and private tertiary care hospitals of Peshawar. The study duration was 6 months (10 September 2021-10 Febuary 2022) after the approval of research proposal. The sampling method was non probability convenient sampling. The inclusion criteria were health professionals involved in the care of the COVID 19 patients like pulmonogists, physicians, trainee doctors, nurses and chest physiotherapists. Exclusion criteria were the doctors from other specialties who were not taking in the management of such patients. Empathy scale was used to collect responses of the participants .The data was analyzed using SPSS latest version Results: Significant association was seen between Consultants, Nurses and PGRs with that they were not interested in patient’s personal matters as these are not relevant to medical treatment. i.e. p-value <0.001. Significant association was seen between Consultants, Nurses and PGRs they Viewed things from patient’ perspectives might confuse me and make me too distracted to take the right clinical decision (cognitive). I.e. p-value=0. 026 Conclusion: The level of empathy did get affected to a colossal extent during the COVID-19 pandemic as reflected by the above results. Keywords: Empathy, COVID 19, healthcare professionals